Optimalisasi Upaya Administratif Dalam Peradilan Tata Usaha Negara - Rasji, Rasji; Michellena, Michellena; Syamila, Najma (Jurnal Ilmiah Wahana Pendidikan, 2024)
As a country that embraces the concept of welfare state, and implicitly can be seen in the general explanation of the 1945 Constitution. The state plays a key role in implementing or realising the protection and promotion of the economic and social welfare of its citizens. In practice, the two are often at odds or have different views and opinions, such as when the state issues regulations or issues certain policies, some citizens reject them because they are not in accordance with the will and needs of the people. In the writing process using normative juridical research methods, which are sourced entirely based on secondary data. In the process of resolving the State Administration, there are two solutions, namely administratively and a lawsuit to the court. In its implementation, the Administrative Court is still less effective because there are no firmer regulations governing the execution of the Administrative Court's decision itself, in fact the execution of the Administrative Court is still difficult to carry out due to the lack of cooperation from the Administrative Court officials.